Usability Testing Of Web Mapping Portals - Petr Voldán (Geoinformatics FCE CTU, 2011)
This study presents a usability testing as method, which can be used to improve controlling of web map sites. Study refers to the basic principles of this method and describes particular usability tests of mapping sites. In this paper are identified potential usability problems of web sites: Amapy.cz, Google maps and Mapy.cz. The usability testing was focused on problems related with user interfaces, addresses searching and route planning of the map sites.